(untitled) (Research, Society and Development, 2021)
In the search for an alternative chemical control against Aedes aegypti, many researches are developed and encouraged in order to find new bioinsecticide substances of plant origin. Thus, the objective of this work was to evaluate the larvicidal effect of the essential oil of rue (Ruta graveolens Linneau) on third instar Aedes aegypti larvae. The identification of chemical components present in the essential oil of R. graveolens Linneau was performed by gas chromatography-mass spectrometry (GC/MS). Larvicidal activity was determined using the Reed-Muench and Pizzi methods in Aedes aegypti larvae. The results showed that the essential oil of rue had the highest larvicidal activity, at a concentration of 61,641 ± 1,72 μg mL-1. The mortality efficiency of Aedes aegypti may be related to the presence of 2-nonanone and 2-undecanone (methylketones) in the rue essential oil, important components of recognized efficacy as an insecticide. Thus, it can be seen that the essential oil under study has chemical compounds with a larvicidal effect against A. aegypti.